2007
DOI: 10.1177/193229680700100211
|View full text |Cite
|
Sign up to set email alerts
|

Significant Insulin Dose Errors May Occur if Blood Glucose Results are Obtained from Miscoded Meters

Abstract: Objective:The objective of this study was to determine inaccuracies of miscoded blood glucose (BG) meters and potential errors in insulin dose based on values from these meters. Research Design:Fasting diabetic subjects at three clinical centers participated in a 2-hour meal tolerance test. At various times subjects' blood was tested on five BG meters and on a Yellow Springs Instruments laboratory glucose analyzer. Some meters were purposely miscoded. Using the BG values from these meters, along with three ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 12 publications
(11 reference statements)
1
43
0
5
Order By: Relevance
“…Our previous study demonstrated that miscoded meters have the potential of producing such values. 8 This paper examines potential glycemic outcomes from insulin doses administered on the basis of improperly coded meters. Insulin dose recommendations based on commonly used correction formulas may result in serious adverse clinical outcomes if glucose data are wrong.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study demonstrated that miscoded meters have the potential of producing such values. 8 This paper examines potential glycemic outcomes from insulin doses administered on the basis of improperly coded meters. Insulin dose recommendations based on commonly used correction formulas may result in serious adverse clinical outcomes if glucose data are wrong.…”
Section: Resultsmentioning
confidence: 99%
“…10 We have shown that with deliberately miscoded meters, there was a potential for insulin errors of as much as +5 units when a correction scheme is used to determine an insulin dose, given that a glucose meter is miscoded. 8 In deliberately miscoded meters, errors as great as -36.23% [standard deviation (SD) 6.34] or +26.53% (SD 12.45) relative to the reference YSI glucose were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A correction dose of insulin based on inaccurately high readings could have the potential for severe hypoglycemia as shown in research. 1 Failure to take a correction dose for an inaccurately low reading could allow hyperglycemia to continue. 1 Based on the Raines study, 1 miscoding does contribute to errors in blood glucose results.…”
Section: Resultsmentioning
confidence: 99%
“…The training status of all glucometer operators included healthcare providers and family members, but details remained unknown. Raine et al concluded that up to 16% of patients do not use glucometers properly and this leads to ±33% errors [7].…”
Section: Discussionmentioning
confidence: 99%